Crystallographic and geometry-optimization study on 2, 4, 6-trinitrophenol: 3-methyl-4-nitropyridine N-oxide (1/1) - Zain, Sharifuddin Md; Ng, S.W.; Mohammad, M.R. (Faculty of Science, University of Malaya, 2005)
In the crystal structure of 2,4,6-trinitrophenol:3-methyl-4-nitropyridine N-oxide (1/1) (TNP:POM), the hydroxyl group of TNP is hydrogen bonded to the N-oxide oxygen atom of POM [O⋯O = 2.607(5) Å], and adjacent molecules are linked by a supramolecular C-H$_{aromaric}$⋯O$_{N-oxide}$ interaction across a center-of-inversion to form a weakly-held TNP:POM dimer. The ortho-nitro group that engages in hydrogen bonding is nearly coplanar with the aromatic ring of the TNP moiety whereas the ortho-nitro group that is free is severely twisted. Geometry-optimization calculations at B3LYP/6-31G* level was also carried out for comparison.